1980
DOI: 10.1136/gut.21.4.324
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of maximal acid output and gastrin response to meals in Chinese and Scottish normal and duodenal ulcer subjects.

Abstract: SUMMARY Maximal acid output (MAO) after pentagastrin stimulation and gastrin response to a standard meal was studied in 100 control and 200 duodenal ulcer subjects from each of two ethnic groups, Scots and Chinese. The acid output was significantly higher in the Scots than in the Chinese for both controls and duodenal ulcer patients. Despite correction for differences in body stature by expressing MAO as a function of the body weight, these differences persisted. In 45 pairs of closely matched patients with du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
60
3
5

Year Published

1983
1983
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(73 citation statements)
references
References 14 publications
5
60
3
5
Order By: Relevance
“…An analogous situation was observed in the acid secretory pattern in an earlier study reported by us, in which acid output was signi®cantly greater in the Scottish population compared to Chinese, both in normal controls and duodenal ulcer patients. 29 It will be interesting to perform an isotope-labelled urea study in the Chinese population to study the distribution, delivery and emptying of 13 C-urea as described by Atherton et al 26 In conclusion, we have shown that for a low dose 75 mg 13 C-urea breath test protocol with or without a test meal, the optimal measurement interval was 30 min and the optimal DOB cut-off value was 5%. This low dose protocol without a test meal was highly accurate in the diagnosis of H. pylori infection in a Chinese population.…”
Section: Discussionmentioning
confidence: 63%
“…An analogous situation was observed in the acid secretory pattern in an earlier study reported by us, in which acid output was signi®cantly greater in the Scottish population compared to Chinese, both in normal controls and duodenal ulcer patients. 29 It will be interesting to perform an isotope-labelled urea study in the Chinese population to study the distribution, delivery and emptying of 13 C-urea as described by Atherton et al 26 In conclusion, we have shown that for a low dose 75 mg 13 C-urea breath test protocol with or without a test meal, the optimal measurement interval was 30 min and the optimal DOB cut-off value was 5%. This low dose protocol without a test meal was highly accurate in the diagnosis of H. pylori infection in a Chinese population.…”
Section: Discussionmentioning
confidence: 63%
“…[4][5][6] The parietal-cell mass in Asian subjects is smaller than that in white subjects. 24 We therefore did not consider pH monitoring necessary. Most episodes of recurrent bleeding occurred in the first 72 hours after endoscopy in both groups -the period of infusion.…”
Section: Discussionmentioning
confidence: 99%
“…A similar observation was reported with regard to the parietal cell mass and acid secretory capacity of Asian patients with duodenal ulcer, which are only slightly more than half the values of Caucasian patients despite correction for body stature. 10 14 Furthermore, ethnic differences in gastric emptying have been reported previously. 15 Further physiological studies on gastric emptying in the Chinese population are warranted.…”
Section: 12mentioning
confidence: 99%